IMLEMENTASI KEBIJAKAN REVITALISASI PASAR TRADISIONAL SARIJADI OLEH PD. PASAR BERMARTABAT KOTA BANDUNG - YUYUN MULYATI; ANI SURTIANI (Prodi Ilmu Administrasi Negara, Universitas Al Ghifari, 2020)
This study aims to analyze and describe the implementation activities of revitalization policy of Traditional Market Sarijadi by PD. Pasar Bermartabat of Bandung City which includes organization, interpretation and application. This research uses qualitative approach with descriptive method of analysis. Data collection techniques were conducted with in-depth interviews, observations and literature studies. The results of the study indicate that the organization has not been supported by human resources and facilities in accordance with needs, while the funds are sufficient. Establishing a thematic organic vegetable market for Sarijadi Market and direct socialization to higher education and comparative study followed by traders and employees and Directors of PD. Pasar Bermartabat of Bandung city is an organizing method. Interpretation of activities related to work programs and revitalization activities has not been supported by future guidelines and targets because no Strategic Plan has been determined yet. While the application activity of the Implementation of Sarijadi Traditional Market Revitalization Policy by PD. Pasar Bermartabat of Bandung City associated with the service has been using information technology for levy and maintenance services of Business Registration Letters and promotions for rental offerings. Research report on the Implementation of Sarijadi Traditional Market Revitalization Policy by PD. Pasar Bermartabat Bandung City has not yet run. Research suggestions need to be established immediately in the Strategic Plan, training and training facilities are needed, the addition of infrastructure.